2004
DOI: 10.1021/jm0400294
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in Vitro Pharmacology, Structure−Activity Relationships, and Pharmacokinetics of 3-Alkoxy-2-amino-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic Acid Derivatives as Potent and Selective Group II Metabotropic Glutamate Receptor Antagonists

Abstract: Novel group II metabotropic glutamate receptor (mGluR) antagonists, 3-alkoxy-2-amino-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid derivatives 11 and 12, were discovered by the incorporation of a hydroxy or alkoxyl group onto the C-3 portion of selective and potent group II mGluR agonist 5, (1R,2S,5R,6R)-2-amino-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid. Among these compounds, (1R,2R,3R,5R,6R)-2-amino-3-(3,4-dichlorobenzyloxy)-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (-)-11be (MGS0039) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…LY341495 has nanomolar affinities for mGlu 2/3 receptors [109,110]. MGS0039 containing a bicyclo[3.1.0]hexane ring system was reported to have nanomolar affinities for mGlu 2/3 receptors [111]. The series of mGlu 2/3 receptors antagonists that have amino acid moieties are found at low levels in the CNS.…”
Section: Mglu2/3 Receptor Antagonistsmentioning
confidence: 99%
“…LY341495 has nanomolar affinities for mGlu 2/3 receptors [109,110]. MGS0039 containing a bicyclo[3.1.0]hexane ring system was reported to have nanomolar affinities for mGlu 2/3 receptors [111]. The series of mGlu 2/3 receptors antagonists that have amino acid moieties are found at low levels in the CNS.…”
Section: Mglu2/3 Receptor Antagonistsmentioning
confidence: 99%
“…MGS0039, its prodrugs ( Fig. 1), and MG0037 (3-(3,4-difluorobenzyloxy)-2-amino-6-fluorobicyclo[3.1.0]hexane-2,6-dicarboxylic acid) (internal standard) were synthesized in Taisho Research Laboratories as described previously (Nakazato et al, 2004). NADP ϩ and glucose 6-phosphate were obtained from Oriental Yeast Co., Ltd. (Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…MGS0039 (3-(3,4-dichlorobenzyloxy)-2-amino-6-fluorobicyclo-[3.1.0]hexane-2,6-dicarboxylic acid) is a potent and selective antagonist for group II mGluRs as determined by attenuation of glutamateinduced inhibition of forskolin-evoked cAMP formation in Chinese hamster ovary cells expressing mGluR2 (IC 50 ϭ 20 nM) or mGluR3 (IC 50 ϭ 24 nM) Nakazato et al, 2004). We previously reported that group II mGluR antagonists exhibited antidepressant potential in experimental animal models such as the rat forced swimming and mouse tail suspension tests .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 a number of experiments described the antidepressant-like activity of ligands of the mGlu 2/3 receptors. The best known selective and brain penetrating ligands of mGlu 2/3 receptors is MGS0039 (Nakazato et al, 2004). Another antagonist LY341495, is able to bind the third group of mGlu receptors too (Chung et al, 1997).…”
Section: The Role Of Group II Mglu Receptors In the Mechanism Of Actimentioning
confidence: 99%